2017
DOI: 10.1002/biot.201600558
|View full text |Cite
|
Sign up to set email alerts
|

The application of constitutively solvent‐tolerant P. taiwanensis VLB120ΔCΔttgV for stereospecific epoxidation of toxic styrene alleviates carrier solvent use

Abstract: For whole-cell biotransformations involving toxic organic compounds, two-liquid phase setups are typically applied employing an apolar extractive phase. Bis(2-ethylhexyl)phthalate (BEHP) has proven to be an ideal solvent for stereospecific styrene epoxidation with recombinant E. coli, providing excellent extractive properties and a high biocompatibility. In eco-efficiency evaluations, BEHP, however, has been identified as a critical factor regarding costs and environmental impact. In this study, the constituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…Under these conditions, P. taiwanensis VLB120Δ C Δ ttgV_AeGFP did not show higher epoxidation activities than the VLB120Δ C_AeGFP strain (Figure ), which was in contrast to their behavior in resting‐cell assays (Supporting Information Figure S2) and in two‐liquid phase batch cultures of the Δ C and Δ C Δ ttgV strains (Volmer et al, ). After 3 hr, both strains reached a maximal activity of 30–40 U/g CDW , which decreased toward the end of the biotransformation.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Under these conditions, P. taiwanensis VLB120Δ C Δ ttgV_AeGFP did not show higher epoxidation activities than the VLB120Δ C_AeGFP strain (Figure ), which was in contrast to their behavior in resting‐cell assays (Supporting Information Figure S2) and in two‐liquid phase batch cultures of the Δ C and Δ C Δ ttgV strains (Volmer et al, ). After 3 hr, both strains reached a maximal activity of 30–40 U/g CDW , which decreased toward the end of the biotransformation.…”
Section: Resultsmentioning
confidence: 91%
“…Constitutively solvent‐tolerant P. taiwanensis VLB120∆ C ∆ ttgV has been shown to exhibit two‐fold improved styrene epoxidation activities compared with P. taiwanensis VLB120∆ C (Volmer et al, , ). The substitution of the styA gene with a styA‐eGFP fusion construct allowed determining the intracellular oxygenase amount and revealed that increased oxygenase levels in the constitutively solvent‐tolerant mutant constitute one, but not the only reason for the observed elevated activities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, titanium silicate molecular sieves, heteropoly compounds and metal complexes are often used to catalyze the epoxidation of styrene to form styrene oxide, but they are limited by expense and low activity and stability respectively. Volmer et al . used a whole‐cell biocatalytic method to facilitate the catalytic reaction of Pseudomonas taiwanensis VLB120ΔCΔttgV with organic solvent tolerance to diphenyl phthalate environments, showing relatively high styrene epoxidation activity.…”
Section: Applications Of Organic Solvent‐tolerant Bacteriamentioning
confidence: 99%